Does applying a circular business model lead to organizational resilience? Mediating effects of industry 4.0 and customers integration - Lopes de Sousa Jabbour, Ana Beatriz; Latan, Hengky; Chiappetta Jabbour, Charbel Jose; Seles, Bruno Michel Roman Pais [UNESP] (Elsevier, 2023)
This article presents groundbreaking research that analyses the direct relationship between the adoption of circular economy business models and organizational resilience. In addition, the research model tests the mediating effects of both the adoption of Industry 4.0 technologies and customer integration initiatives on that relationship. The data used was collected from manufacturing companies operating in an emerging market and was analyzed using covariance structure analysis. The research hypotheses were confirmed, supporting the assumption that adopting a circular economy model enhances organizational resilience. Industry 4.0 technologies and customer integration initiatives are shown to be sources of dynamic capabilities that enable firms to recognize and adapt to market opportunities and threats, and to prepare resources accordingly to achieve resilience by means of business circularity.
Keywords: Circular economy; Emerging market; Industry 4.0; Resilience; Sustainability